2017
DOI: 10.1021/acsomega.7b01400
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Triggered Self-Assembly of Linear Polymer into Nanoparticles for Simultaneous Delivery of Hydrophobic and Hydrophilic Drugs in Breast Cancer Cells

Abstract: Breast cancer is the most devastating disease among females globally. Conventional chemotherapeutic regimen relies on the use of highly cytotoxic drugs as monotherapy and combination therapy leading to severe side effects to the patients as collateral damage. Moreover, combining hydrophobic and hydrophilic drugs create erratic biodistribution and suboptimal medicinal outcome. Hence, packaging multiple drugs of diverse mechanisms of action and biodistribution for safe delivery into tumor tissues with optimal do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Linear polymers are mostly used for drug delivery to specific cells and tissues [8]. Recently provided studies, however, demonstrated the high efficiency of a branched copolymer of dextran-polyacrylamide, both as a nanocarrier for drug delivery and as a matrix for the preparation of new nanosystems for antitumor photodynamic therapy [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Linear polymers are mostly used for drug delivery to specific cells and tissues [8]. Recently provided studies, however, demonstrated the high efficiency of a branched copolymer of dextran-polyacrylamide, both as a nanocarrier for drug delivery and as a matrix for the preparation of new nanosystems for antitumor photodynamic therapy [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Synthetic biomaterials are often more suitable for such applications than natural biomaterials; [4][5][6] examples include modified carriers based on natural and synthetic polymers, metal complex, proteins, peptides, hydrogels, and ionic liquids (ILs); all of which exhibit considerable potential for cancer drug delivery system. [7][8][9][10][11][12] Ionic liquids (ILs) are beneficial for the development of sensors, electrochemistry, and in the development of catalysts and pharmaceuticals, and drug carriers. ILs drug carriers have been widely used in anticancer chemotherapy because of their excellent drug carrier and binding properties.…”
Section: Introductionmentioning
confidence: 99%
“…Such biomaterials are non‐toxic and increase thermal stability, drug encapsulation efficiency, biodegradability, biocompatibility, and a high degree of porosity for cell penetration [1–3] . Synthetic biomaterials are often more suitable for such applications than natural biomaterials; [4–6] examples include modified carriers based on natural and synthetic polymers, metal complex, proteins, peptides, hydrogels, and ionic liquids (ILs); all of which exhibit considerable potential for cancer drug delivery system [7–12] . Ionic liquids (ILs) are beneficial for the development of sensors, electrochemistry, and in the development of catalysts and pharmaceuticals, and drug carriers.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 There is an enormous attempt to explore the role/ function of synthetic biomaterials used in drug delivery applications. 3 Currently, synthetic and natural polymers, metal complexes, peptides, proteins, and hydrogels are used for the development of anticancer drug delivery systems, [4][5][6][7][8] which reduce some disadvantages over conventional anticancer treatments such as poor solubility, low biodegradability, toxic nature, and poor intracellular penetration, retention time and sustainable release of encapsulated drugs. 9 A signicant number of nanoparticles such as inorganic nanoparticles or other polymeric/liquid nanoparticles have also been used in developing drug carrier systems.…”
Section: Introductionmentioning
confidence: 99%